Association of PPP2CA polymorphisms with systemic lupus erythematosus susceptibility in multiple ethnic groups (2011)
Objective T cells from patients with systemic lupus erythematosus (SLE) express increased amounts of PP2Ac, which contributes to decreased production of interleukin-2 (IL-2). Because IL-2 is important in the regulation of several aspects of the immune response, it has been proposed that PP2Ac contributes to the expression of SLE. This study was designed to determine whether genetic variants of PPP2AC are linked to the expression of SLE and specific clinical manifestations and account for the increased expression of PP2Ac. Methods We conducted a trans-ethnic study of 8,695 SLE cases and 7,308 controls of 4 different ancestries. Eighteen single-nucleotide polymorphisms (SNPs) across PPP2CA were genotyped using an Illumina custom array. PPP2CA expression in SLE and control T cells was analyzed by real-time polymerase chain reaction. Results A 32-kb haplotype comprising multiple SNPs of PPP2CA showed significant association with SLE in Hispanic Americans, European Americans, and Asians, but not in African Americans. Conditional analyses revealed that SNP rs7704116 in intron 1 showed consistently strong association with SLE across Asian, European American, and Hispanic American populations (odds ratio 1.3 [95% confidence interval 1.14-1.31], meta-analysis P = 3.8 × 10 -7). In European Americans, the largest ethnic data set studied, the risk A allele of rs7704116 was associated with the presence of renal disease, anti-double-stranded DNA, and anti-RNP antibodies. PPP2CA expression was ?2-fold higher in SLE patients carrying the rs7704116 AG genotype than those carrying the GG genotype (P = 0.007). Conclusion Our data provide the first evidence of an association between PPP2CA polymorphisms and elevated PP2Ac transcript levels in T cells, which implicates a new molecular pathway for SLE susceptibility in European Americans, Hispanic Americans, and Asians. Copyright © 2011 by the American College of Rheumatology.